Recent Advances on the Molecular Mechanism and Clinical Trials of Venous Thromboembolism - Huang SL; Xin HY; Wang XY; Feng GG; Wu FQ; Feng ZP; Xing Z; Zhang XH; Xin HW; Luo WY (Dove Medical Press, 2023)
Shao-Li Huang,1- 3,* Hong-Yi Xin,4,5,* Xiao-Yan Wang,4,5,* Guang-Gui Feng,3 Fu-Qing Wu,3 Zhi-Peng Feng,6 Zhou Xing,2 Xi-He Zhang,4,5 Hong-Wu Xin,4,7,8 Wen-Ying Luo1 1Medical Laboratory Center, Affiliated Hospital of Guangdong Medical University, Zhanjiang, Guangdong, 524400, People's Republic of China; 2First Clinical College, Guangdong Medical University, Guangdong, 524400, People's Republic of China; 3Clinical laboratory, Lianjiang People's Hospital, Guangdong, 524400, People's Republic of China; 4Doctoral Scientific Research Center, Lianjiang People's Hospital, Guangdong, 524400, People's Republic of China; 5Guangdong Medical University Affiliated Lianjiang People's Hospital, Guangdong, 524400, People's Republic of China; 6Department of Gastroenterology, Yueyang Hospital Affiliated to Hunan Normal University, Yueyang, Hunan, 414000, People's Republic of China; 7Laboratory of Oncology, Center for Molecular Medicine, School of Basic Medicine, Faculty of Medicine, Yangtze University, Jingzhou, Hubei, 434023, People's Republic of China; 8Research Centre of Molecular Medicine, Medical College of Chifeng University, Chifeng, Inner Mongolian Autonomous Region, 024000, People's Republic of China*These authors contributed equally to this workCorrespondence: Wen-Ying Luo, Medical laboratory Center, Affiliated Hospital of Guangdong Medical University, 57th South Renmin Road, Zhanjiang, 524001, People's Republic of China, Tel +86 18312728748, Email luo_wenying@126.com Xi-He Zhang, Doctoral Scientific Research Center, Lianjiang People's Hospital, Guangdong, 524400, People's Republic of China, Tel +86 19126491230, Email hljsnjx@163.comAbstract: Venous thromboembolism is a condition that includes deep vein thrombosis and pulmonary embolism. It is the third most common cardiovascular disease behind acute coronary heart disease and stroke. Over the past few years, growing research suggests that venous thrombosis is also related to the immune system and inflammatory factors have been confirmed to be involved in venous thrombosis. The role of inflammation and inflammation-related biomarkers in cerebrovascular thrombotic disease is the subject of ongoing debate. P-selectin leads to platelet-monocyte aggregation and stimulates vascular inflammation and thrombosis. The dysregulation of miRNAs has also been reported in venous thrombosis, suggesting the involvement of miRNAs in the progression of venous thrombosis. Plasminogen activator inhibitor-1 (PAI-1) is a crucial component of the plasminogen-plasmin system, and elevated levels of PAI-1 in conjunction with advanced age are significant risk factors for thrombosis. In addition, it has been showed that one of the ways that neutrophils promote venous thrombosis is the formation of neutrophil extracellular traps (NETs). In recent years, the role of extracellular vesicles (EVs) in the occurrence and development of VTE has been continuously revealed. With the advancement of research technology, the complex regulatory role of EVs on the coagulation process has been gradually discovered. However, our understanding of the causes and consequences of these changes in venous thrombosis is still limited. Therefore, we review our current understanding the molecular mechanisms of venous thrombosis and the related clinical trials, which is crucial for the future treatment of venous thrombosis.Keywords: venous thromboembolism, miRNA, neutrophil extracellular traps, plasminogen activator inhibitor-1, EVs, inflammatory factor